2019
DOI: 10.1111/exsy.12415
|View full text |Cite
|
Sign up to set email alerts
|

Quantum‐inspired genetic programming model with application to predict toxicity degree for chemical compounds

Abstract: Cheminformatics plays a vital role in maintaining large amounts of chemical data. The reliable prediction of toxic effects of chemicals in living systems is highly desirable in domains such as cosmetics, drug design, food safety, and the manufacturing of chemical compounds. Toxicity prediction requires several new approaches for knowledge discovery from data to paradigm composite associations between the modules of the chemical compound; the computational demands of such techniques increase greatly with the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A network with 75 layers to categorize various blood cell types with an accuracy of 0.99 on average is proposed. A genetic programming technique based on quantum computing was proposed by Darwish et al (2019) to increase prediction accuracy in linear equations for a more precise determination of the degree of toxicity. The outcomes showed that the proposed model performs better than the neural network model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A network with 75 layers to categorize various blood cell types with an accuracy of 0.99 on average is proposed. A genetic programming technique based on quantum computing was proposed by Darwish et al (2019) to increase prediction accuracy in linear equations for a more precise determination of the degree of toxicity. The outcomes showed that the proposed model performs better than the neural network model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main contribution behind this paper is to present how the algorithm is tailored to the problem, containing crossover and mutation operators furthermore setting the overall framework for the utilization of quantum ideas in varied applications. In addition, QIEA is applied along with genetic programming to improve prediction accuracy of toxicity degree of chemical compounds [30]. In this work, the accuracy of linear equation that used to calculate the degree of toxicity increased as a result of using genetic programming.…”
Section: Related Workmentioning
confidence: 99%
“…The main contribution behind this paper is to present how the algorithm is tailored to the problem, containing crossover and mutation operators, furthermore setting the overall framework for the utilization of quantum ideas in varied applications. In addition, QIEA is applied along with genetic programming to improve prediction accuracy of toxicity degree of chemical compounds [29]. In this work, the accuracy of the linear equation that was used to calculate the degree of toxicity increased as a result of using genetic programming.…”
Section: Related Workmentioning
confidence: 99%